(3JMQjQ cJGH GhWhdhbS aj GdWdhY hGdZQhHs - (3GhWhdhbSs
(3ChdgG (B:s
(3HYO GdOjHGLI GdebGdI GdChdj TcdkG UOQ jbGd (B: (3dHYV WdhYGJ GdchGcH hZQhHGJgG s
(3BNQgG (B:s
(3hPdc eG GQOfGg BNQ GdebGdI GdKGfjI hJe HJeGegG GdcJGH s
(3Vef eLehY , JQJjHgG (B: 15s
(3hgh ebGdGJ h (B36 (3TcdkGs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(1760) s
Keywords: (3eJaQbGJs